Double-layer cigarette case and manufacturing process thereof

By combining a double-layer cigarette box design with a functional coating, the problems of poor preservation and insufficient environmental friendliness of cigarette boxes are solved, achieving a highly efficient, environmentally friendly, and biodegradable tobacco storage solution.

CN121106927APending Publication Date: 2025-12-12WUHAN YIJIN PACKAGING PRINTING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511564980.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-30
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing cigarette boxes have limited functionality, poor preservation effect, and are not environmentally friendly. They are unable to effectively delay the flavor deterioration and quality decline of tobacco caused by oxidation and moisture absorption. Furthermore, traditional plastic packaging is difficult to degrade, putting pressure on the environment.

Method used

The cigarette box features a double-layer design. The upper and lower layers are made of biodegradable materials such as polylactic acid and polyhydroxyalkanoate, respectively. The inner box contains chiral BIDIME-selenool as a functional additive, and the outer surface is coated with a cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework functional coating. A stable coating is formed through physical mixing and chemical reaction, achieving multiple protective functions.

Benefits of technology

It effectively delays tobacco oxidation and deterioration, maintains the original flavor, stabilizes the storage environment, prevents cross-contamination of flavors, and is also environmentally friendly and biodegradable, avoiding the health effects of functional additive migration and providing brand protection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121106927A_ABST
    Figure CN121106927A_ABST
Patent Text Reader

Abstract

The invention discloses a double-layer cigarette case and a manufacturing process thereof in the technical field of tobacco packaging, the cigarette case is composed of an upper-layer cigarette case and a lower-layer cigarette case, the upper-layer cigarette case comprises an upper-layer panel and an upper-layer inner case, and the lower-layer cigarette case comprises a lower-layer panel and a lower-layer inner case; the panel and the inner box take biodegradable polyester as a matrix, and a chiral selenol compound with an anti-oxidation effect is added; the outer surfaces of the upper-layer cigarette case and the lower-layer cigarette case are coated with functional coatings containing cobalt-based zeolite imidazole frames, and the functional coatings are used for adjusting humidity and adsorbing peculiar smell. According to the upper-layer cigarette case and the lower-layer cigarette case provided by the invention, the fresh-keeping effect and the storage stability of tobacco products are remarkably improved, and meanwhile, environmental protection and anti-counterfeiting functions are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of tobacco packaging technology, specifically to a double-layer cigarette box and its manufacturing process. Background Technology

[0002] Traditional cigarette boxes mostly use a single-layer paper or plastic structure, offering limited functionality and failing to meet consumers' diverse requirements for tobacco product preservation, moisture protection, and odor isolation. With rising consumer demand, double-layer or multi-compartment cigarette box designs have emerged, using physical separation to package different types of tobacco. However, the materials themselves still lack functionality and cannot effectively slow down flavor degradation and quality decline caused by oxidation and moisture absorption. While existing technologies have attempted to add oxygen absorbers or desiccants to packaging materials, these methods often suffer from problems such as crude addition methods, limited functionality, poor material compatibility, and potential tobacco contamination. Particularly concerning is environmental protection; the widespread use of traditional plastic packaging is difficult to degrade, placing continuous pressure on the environment. Therefore, developing a new type of cigarette box that integrates compartmentalized storage, active preservation, and environmental friendliness has become a pressing technical challenge for the industry.

[0003] In the field of materials science, biodegradable polyester materials such as polylactic acid (PLA) have been attempted for application in the packaging industry, but their functional modification remains a challenge. Simply blending functional additives directly into the substrate often results in drawbacks such as easy migration, easy precipitation, and short-lasting effects. On the other hand, in advanced chemistry, chiral catalytic materials and metal-organic frameworks exhibit superior performance in antioxidant and selective adsorption, respectively. However, how to stably and efficiently integrate these high-performance materials into everyday packaging products and achieve large-scale production remains a lack of feasible technical solutions. Existing packaging processes struggle to coordinate the processing characteristics of materials with different properties; for example, the combination of a hydrophobic matrix and a hydrophilic functional coating is a common technical bottleneck.

[0004] In summary, existing cigarette boxes have significant shortcomings in terms of product structure, functionality, and environmental friendliness. There is an urgent need for an innovative design that can integrate advanced functional materials into environmentally friendly base materials through appropriate processes, thereby creating a novel, functional, and sustainable double-layered cigarette box to address practical pain points in tobacco storage and meet the demands of sustainable development. Summary of the Invention

[0005] The purpose of this invention is to provide a double-layer cigarette box and its manufacturing process, which solves the technical problems of existing cigarette boxes having single function, poor preservation effect, and being environmentally unfriendly.

[0006] The present invention achieves the above objectives through the following technical solutions: A double-layer cigarette box comprises an upper cigarette box and a lower cigarette box. The upper cigarette box includes an upper panel and an upper inner box, and the lower cigarette box includes a lower panel and a lower inner box. The upper and lower panels comprise the following raw materials in parts by weight: polylactic acid: 65-75 parts by weight; polyhydroxyalkanoate: 20-30 parts by weight; chiral BIDIME-selenool: 0.4-0.6 parts by weight; triethyl acetylacetate: 4-5 parts by weight. The upper and lower inner boxes comprise the following raw materials in parts by weight: polylactic acid: 70-8... 0 parts by weight; polyhydroxyalkanoate: 15-25 parts by weight; chiral BIDIME-selenool: 0.1-0.3 parts by weight; triethyl acetylacetate: 3-4 parts by weight; the upper inner box and the lower inner box are coated with a functional coating, the functional coating comprising the following raw materials in parts by weight: cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework: 0.8-1.2 parts by weight; polyvinyl alcohol: 4-6 parts by weight; chitosan: 15-25 parts by weight; glycerol: 2-4 parts by weight; water: 75-85 parts by weight.

[0007] According to a preferred embodiment of the present invention, the amount of raw materials used in the upper panel and the lower panel may be the same or different.

[0008] According to a preferred embodiment of the present invention, the upper panel and the lower panel are prepared by the same method, including the following preparation steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 175°C to produce masterbatch, which was then calendered.

[0009] According to a preferred embodiment of the present invention, the amount of raw materials used in the upper inner box and the lower inner box may be the same or different.

[0010] According to a preferred embodiment of the present invention, the upper inner box and the lower inner box are prepared by the same method, including the following preparation steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 185°C to produce masterbatch, which was then calendered.

[0011] According to a preferred embodiment of the present invention, the preparation method of the chiral BIDIME-selenool includes: A1, under nitrogen protection, dissolving (S)-BIDIME in anhydrous tetrahydrofuran and cooling to -76~-80℃; adding n-butyllithium and stirring to obtain a reaction solution; dispersing selenium powder in anhydrous tetrahydrofuran and adding it dropwise to the reaction solution, and then heating to room temperature after the addition is complete; A2, after the reaction is completed, the crude product obtained by rotary evaporation is purified by modified diatomaceous earth column chromatography.

[0012] In this invention, the (S)-BIDIME, chemically named (S)-3-(tert-butyl)-4-(2,6-dimethoxyphenyl)-2,3-dihydrobenzo[d][1,3]oxaphosphacyclopentadiene, is a rigid skeleton monophosphine ligand with a p-chiral center (i.e., the chiral center is located on a phosphorus atom) and a molecular formula of C19H23O3P.

[0013] In this invention, the preparation mechanism of chiral BIDIME-selenool is based on organolithium chemistry and nucleophilic substitution reaction. Under anhydrous and oxygen-free conditions, the C-H bond adjacent to the phosphorus atom in the chiral BIDIME molecule undergoes a deprotonation reaction with the strong base n-butyllithium, generating a highly reactive carbanion intermediate. This carbanion acts as a strong nucleophile, attacking the elemental selenium atom and forming a carbon-selenium bond through nucleophilic substitution, ultimately yielding the target product, chiral BIDIME-selenool. The entire reaction process needs to be strictly controlled in a low-temperature, inert atmosphere to avoid damage to the organolithium reagent by air and moisture, ensuring the high efficiency and selectivity of the reaction. The mechanism of the modified diatomaceous earth purification step lies in the fact that its surface is modified with dimethylcarbamoyl chloride and p-methoxycinnamoyl chloride, introducing functional groups with specific polarity and steric hindrance. These functional groups selectively adsorb reaction byproducts and unreacted raw materials through polar interactions and steric hindrance effects, thereby achieving efficient separation and purification of chiral BIDIME-selenool.

[0014] According to a preferred embodiment of the present invention, in step A1, the reaction time to room temperature is 12-15 hours.

[0015] According to a preferred embodiment of the present invention, in step A2, the preparation step of the modified diatomaceous earth includes: taking pre-dried diatomaceous earth, dispersing it in anhydrous pyridine, and cooling it to 0-5°C in an ice-water bath; adding dropwise a mixed solution of anhydrous tetrahydrofuran containing dimethylcarbamoyl chloride and p-methoxycinnamoyl chloride under stirring; after the addition is complete, raising the temperature to room temperature for reaction; after the reaction is complete, filtering, washing the solid sequentially with water, ethanol, and diethyl ether until the filtrate is neutral, and finally drying it under vacuum at 78-82°C.

[0016] According to a preferred embodiment of the present invention, the preparation method of the cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework includes: B1, firstly, dissolving 2,6-pyridinedicarboxylic acid and 2-methylimidazolium in a mixed solvent of N,N-dimethylformamide and methanol to obtain a ligand solution; dissolving cobalt nitrate hexahydrate in methanol and adding it dropwise to the ligand solution while stirring during the dropwise addition; after forming a homogeneous solution, adding triethylamine, and transferring the reaction mixture to a high-pressure reactor lined with polytetrafluoroethylene, and reacting at 118-122°C; B2, after the reaction is completed, cooling to room temperature, washing the obtained crystals with N,N-dimethylformamide and methanol, and finally activating them under vacuum at 118-122°C.

[0017] In this invention, the construction mechanism of the cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework belongs to a typical metal-organic framework self-assembly process. This process uses cobalt ions as metal nodes and pyridinedicarboxylic acid and methylimidazolium as mixed organic ligands, forming a three-dimensional porous crystalline material through coordination bonds under solvothermal conditions. The carboxyl oxygen atom and pyridine nitrogen atom in pyridinedicarboxylic acid, as well as the nitrogen atom in methylimidazolium, can all act as electron donors, coordinating with the empty orbitals of cobalt ions to form stable coordination bonds. The addition of triethylamine acts as a deprotonating agent, promoting complete deprotonation of the carboxyl group and enhancing its coordination ability with metal ions. The high-temperature environment provided by the high-pressure reactor provides the necessary activation energy for crystal nucleation and growth, promoting the formation of a thermodynamically stable crystalline phase. The subsequent vacuum activation process removes solvent molecules occupying the framework channels through heating, exposing unsaturated metal sites and channel spaces, giving it humidity responsiveness and gas adsorption capabilities. This unique framework structure enables it to reversibly adsorb and release water molecules according to changes in ambient humidity, while its regular pore structure exhibits a size-selective adsorption effect on odor molecules.

[0018] According to a preferred embodiment of the present invention, in step B1, the reaction time at 118-122°C is 48-50 hours.

[0019] According to a preferred embodiment of the present invention, in step B2, the vacuum activation time at 118-122°C is 6-8 hours.

[0020] The present invention also provides a manufacturing process for the aforementioned double-layer cigarette box, comprising the following steps: S1. Die-cut the upper panel and the lower panel, process the V-groove, and install magnets; S2. Print the upper and lower panel paper with four colors, hot stamping, embossing, and die-cutting respectively. S3. Print monochrome and die-cut the stickers inside the upper panel and the lower panel respectively in sequence; S4. Using a laminating machine, the upper panel face paper processed in step S2 and the upper panel inner sticker processed in step S3 are laminated onto the upper panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied; using a laminating machine, the lower panel face paper processed in step S2 and the lower panel inner sticker processed in step S3 are laminated onto the lower panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied. S5. Die-cut the upper inner box and the lower inner box, process the V-groove, and form the corners; die-cut the upper inner box face paper and the lower inner box face paper; then laminate the upper inner box face paper onto the surface of the upper inner box, and laminate the lower inner box face paper onto the surface of the lower inner box. S6. Disperse the cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework in water, then add polyvinyl alcohol and heat and stir until completely dissolved; then add chitosan and glycerin and continue stirring to obtain a coating solution; apply the coating solution to the outer surfaces of the upper and lower inner boxes treated in step S5, and dry and cure at 48-52℃; after the coating has cured, cut the ribbon and attach it to the surfaces of the upper and lower inner boxes respectively; S7. Assembly of the upper and lower cigarette boxes: Assemble the upper panel processed in step S4 and the upper inner box processed in step S6 to obtain the upper cigarette box; assemble the lower panel processed in step S4 and the lower inner box processed in step S6 to obtain the lower cigarette box; assemble the upper and lower cigarette boxes to obtain the double-layer cigarette box.

[0021] In this invention, both the upper and lower layers of the double-layer cigarette box use polylactic acid and polyhydroxyalkanoate as biodegradable matrices. During melt blending, these materials form a uniform phase through molecular chain entanglement and hydrogen bonding. Chiral BIDIME selenol serves as a key functional additive. Triethyl acetylacetate acts as a plasticizer, improving the material's processability and flexibility by weakening inter-polymer chain forces. The core component of the functional coating, cobalt pyridine dicarboxylic acid zeolite imidazole framework, is then mixed with polyvinyl alcohol and chitosan in an aqueous phase. Chitosan and polyvinyl alcohol form a network film through hydrogen bonding, with glycerol acting as a plasticizer to enhance flexibility. The coating liquid is applied to the outer surfaces of the upper and lower cigarette boxes. During the drying and curing process, moisture evaporation promotes tight cross-linking of the film-forming polymers, while the coating firmly bonds to the outer substrates of the upper and lower cigarette boxes through physical adsorption and potential chemical bonding. The entire system, through the synergistic physical mixing and chemical reaction of its components, gives the cigarette box both environmentally friendly and biodegradable properties, as well as auxiliary functions such as potential adsorption and anti-oxidation brought about by the porous framework and functional additives.

[0022] According to a preferred embodiment of the present invention, in step S6, the coating thickness of the coating liquid applied to the outer surfaces of the upper and lower cigarette boxes is 48-52 μm.

[0023] According to a preferred embodiment of the present invention, in step S6, the stirring time is 2-4 hours.

[0024] The beneficial effects of this invention are as follows: The double-layer cigarette box provided by this invention exhibits significant technological advancements and numerous superior effects. This cigarette box achieves multiple protective functions for tobacco products by adding a specific chiral selenool compound to the inner box substrate and constructing a functional coating containing a cobalt-based zeolite imidazole framework on its outer surface. The chiral selenool compound can efficiently capture and eliminate free radicals generated during tobacco storage, effectively delaying tobacco oxidation and deterioration and preserving the original flavor of the tobacco. The functional coating on the outer surface exhibits excellent humidity regulation capabilities and selective adsorption performance, automatically absorbing and releasing moisture according to changes in ambient humidity, providing a stable storage environment for the tobacco, while effectively adsorbing off-odor molecules generated by tobacco volatilization, preventing cross-contamination of flavors.

[0025] From an environmental and health perspective, this invention demonstrates outstanding comprehensive benefits. The main body of the cigarette box is made of biodegradable polyester materials such as polylactic acid and polyhydroxyalkanoates, fundamentally solving the environmental pollution problems caused by traditional plastic packaging and conforming to the concept of green and sustainable development. The selected functional additives are all stably present in the material matrix through chemical bonding or physical encapsulation, and will not migrate into the tobacco during use, avoiding potential impacts on human health while ensuring long-lasting functional effectiveness. Furthermore, this design can integrate an anti-counterfeiting labeling system, providing brand protection for the product and further enhancing its commercial value. Attached Figure Description

[0026] Figure 1 This is a schematic diagram of the overall frontal three-dimensional structure of the present invention; Figure 2 This is a schematic diagram of the overall horizontally separated three-dimensional structure of the present invention; Figure 3 This is a schematic diagram of the lower inner box structure of the present invention; Figure 4 This is a schematic diagram of the separate upper and lower inner boxes of the present invention.

[0027] In the diagram: 1 upper inner box, 11 upper panel, 2 lower inner box, 21 lower panel. Detailed Implementation

[0028] The following detailed embodiments are only used to further illustrate this application and should not be construed as limiting the scope of protection of this application. Those skilled in the art can make some non-essential improvements and adjustments to this application based on the above application content.

[0029] The following is information on domestic suppliers of the relevant equipment and materials: The polylactic acid was purchased from Chengdu Future Elements Biomaterials Co., Ltd.

[0030] The polyhydroxyalkanoate was purchased from Tianjin Guoyun Biomaterials Co., Ltd.

[0031] The triethyl acetyl citrate was purchased from Hubei Nordina Biotechnology Co., Ltd.

[0032] The polyvinyl alcohol was purchased from Guangxi Guangwei Chemical Co., Ltd.

[0033] The chitosan was purchased from Jiangsu Yitong Biotechnology Co., Ltd.

[0034] The glycerin was purchased from Xi'an Jinxiang Pharmaceutical Excipients Co., Ltd.

[0035] The water was purchased from Nongfu Spring Co., Ltd.

[0036] The (S)-BIDIME was purchased from Zhengzhou Alpha Chemical Co., Ltd.

[0037] The tetrahydrofuran was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0038] The n-butyllithium was purchased from Ningbo EnzymeScience New Energy Technology Co., Ltd.

[0039] The selenium powder was purchased from Changsha Zhongkun Metallurgical Materials Co., Ltd.

[0040] The diatomaceous earth was purchased from Linjiang Xinghui Filter Aid Co., Ltd.

[0041] The dimethylcarbamoyl chloride was purchased from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.

[0042] The p-methoxycinnamoyl chloride was purchased from Wuhan Xinyang Ruihe Chemical Technology Co., Ltd.

[0043] The 2,6-pyridinedicarboxylic acid was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0044] The 2-methylimidazole was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0045] The N,N-dimethylformamide was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0046] The methanol was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0047] The cobalt nitrate hexahydrate was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0048] The triethylamine was purchased from Jinan Dezheng Chemical Co., Ltd.

[0049] The polytetrafluoroethylene-lined high-pressure reactor was purchased from Xinke Pengwei (Weihai) Chemical Machinery Co., Ltd.

[0050] The twin-screw extruder was purchased from Nanjing J&T Electromechanical Co., Ltd.

[0051] Preparation Example 1 This preparation example provides a method for preparing chiral BIDIME-selenool, including the following steps: Under nitrogen protection, 10.0 g of S-BIDIME was dissolved in 200 mL of anhydrous tetrahydrofuran and cooled to -78 °C using a dry ice / acetone bath. At this temperature, 42 mL of a 2.5 M n-butyllithium hexane solution was slowly added dropwise, and the mixture was stirred for 30 minutes to obtain the reaction solution. Separately, 3.2 g of selenium powder was dispersed in 50 mL of anhydrous tetrahydrofuran and added dropwise to the above reaction solution while continuously stirring, controlling the dropping rate to maintain the reaction temperature below -70 °C. After the addition was complete, the reaction system was allowed to naturally warm to room temperature and react for 14 hours. After the reaction was completed, most of the tetrahydrofuran solvent was removed by vacuum distillation using a rotary evaporator at a water bath temperature of 40 °C, yielding an orange-red oily crude product. The crude product was dissolved in a small amount of dichloromethane and purified using a 200 g modified diatomaceous earth-packed chromatography column with petroleum ether / ethyl acetate 10:1 as the eluent. The orange main spot fraction was collected and rotary evaporated to obtain chiral BIDIME-selenool.

[0052] The preparation steps of modified diatomaceous earth include: taking 50g of diatomaceous earth pre-dried at 105℃ for 4 hours, dispersing it in 300mL of anhydrous pyridine, and cooling it to 3℃ in an ice-water bath; slowly adding a 100mL mixture of anhydrous tetrahydrofuran containing 12g of dimethylcarbamoyl chloride and 10g of p-methoxycinnamoyl chloride under mechanical stirring, controlling the addition time to 1 hour; after the addition is complete, raising the temperature to room temperature and reacting for 6 hours; after the reaction is complete, filtering, washing the solid three times with deionized water, twice with anhydrous ethanol, and twice with diethyl ether until the filtrate is neutral, and finally drying it in a vacuum drying oven at 80℃ for 12 hours to obtain modified diatomaceous earth.

[0053] Preparation Example 2 The specific implementation method is the same as in Preparation Example 1, except that the room temperature reaction time in the preparation of chiral BIDIME-selenool is 12 hours, and 11.0g of S-BIDIME and 3.5g of selenium powder are used for the reaction.

[0054] Preparation Example 3 The specific implementation method is the same as in Preparation Example 1, except that the room temperature reaction time in the preparation of chiral BIDIME-selenool is 15 hours, and 9.5g of S-BIDIME and 3.0g of selenium powder are used for the reaction.

[0055] Preparation Example 4 This preparation example provides an upper panel and a lower panel, which comprise the following raw materials in parts by weight: polylactic acid: 70 parts by weight; polyhydroxyalkanoate: 25 parts by weight; chiral BIDIME-selenool: 0.5 parts by weight; triethyl acetylacetate: 4.5 parts by weight; The method for preparing the upper and lower panels includes the following steps: The above-mentioned chiral BIDIME-selenool, polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate were melt-blended and granulated using a twin-screw extruder at a barrel temperature of 175°C to prepare masterbatch, which was then obtained by calendering.

[0056] The chiral BIDIME-selenool provided in this preparation example is the substance obtained in Preparation Example 1.

[0057] Preparation Example 5 This preparation example provides an upper panel and a lower panel, which comprise the following raw materials in parts by weight: polylactic acid: 75 parts by weight; polyhydroxyalkanoate: 20 parts by weight; chiral BIDIME-selenool: 0.4 parts by weight; triethyl acetylacetate: 5.0 parts by weight; The method for preparing the upper and lower panels includes the following steps: The above-mentioned chiral BIDIME-selenool, polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate were melt-blended and granulated using a twin-screw extruder at a barrel temperature of 175°C to prepare masterbatch, which was then obtained by calendering.

[0058] The chiral BIDIME-selenool provided in this preparation example is the substance obtained in Preparation Example 2.

[0059] Preparation Example 6 This preparation example provides an upper panel and a lower panel, which comprise the following raw materials in parts by weight: polylactic acid: 70 parts by weight; polyhydroxyalkanoate: 30 parts by weight; chiral BIDIME-selenool: 0.6 parts by weight; triethyl acetylacetate: 6.0 parts by weight; The method for preparing the upper and lower panels includes the following steps: The above-mentioned chiral BIDIME-selenool, polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate were melt-blended and granulated using a twin-screw extruder at a barrel temperature of 175°C to prepare masterbatch, which was then obtained by calendering.

[0060] The chiral BIDIME-selenool provided in this preparation example is the substance obtained in Preparation Example 3.

[0061] Preparation Example 7 This preparation example provides an upper inner box and a lower inner box, which comprise the following raw materials in parts by weight: polylactic acid: 75 parts by weight; polyhydroxyalkanoate: 20 parts by weight; chiral BIDIME-selenool: 0.2 parts by weight; triethyl acetylacetate: 3.5 parts by weight; The method for preparing the upper inner box and the lower inner box includes the following steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 185°C to produce masterbatch, which was then calendered.

[0062] The chiral BIDIME-selenool provided in this preparation example is the substance obtained in Preparation Example 1.

[0063] Preparation Example 8 This preparation example provides an upper inner box and a lower inner box, which comprise the following raw materials in parts by weight: polylactic acid: 80 parts by weight; polyhydroxyalkanoate: 18 parts by weight; chiral BIDIME-selenool: 0.1 parts by weight; triethyl acetylacetate: 4.0 parts by weight; The method for preparing the upper inner box and the lower inner box includes the following steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 185°C to produce masterbatch, which was then calendered.

[0064] The chiral BIDIME-selenool provided in this preparation example is the substance obtained in Preparation Example 2.

[0065] Preparation Example 9 This preparation example provides an upper inner box and a lower inner box, which comprise the following raw materials in parts by weight: polylactic acid: 70 parts by weight; polyhydroxyalkanoate: 25 parts by weight; chiral BIDIME-selenool: 0.3 parts by weight; triethyl acetylacetate: 3.5 parts by weight; The method for preparing the upper inner box and the lower inner box includes the following steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 185°C to produce masterbatch, which was then calendered.

[0066] The chiral BIDIME-selenool provided in this preparation example is the substance obtained in Preparation Example 3. Example

[0067] This embodiment provides a manufacturing process for the aforementioned double-layer cigarette box, the steps of which include: S1. Die-cut the upper panel and the lower panel, process the V-groove, and install magnets; S2. Print four colors, hot stamp, emboss, and die-cut the upper and lower white cardboard sheets in sequence. S3. Print single-color printing and die-cutting of the yellow specialty paper inside the upper panel and the yellow specialty paper inside the lower panel respectively; S4. Using a laminating machine, the upper panel face paper processed in step S2 and the upper panel inner sticker processed in step S3 are laminated onto the upper panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied; using a laminating machine, the lower panel face paper processed in step S2 and the lower panel inner sticker processed in step S3 are laminated onto the lower panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied. S5. Die-cut, V-groove, and corner-forming the upper and lower inner boxes respectively; die-cut the yellow specialty paper for the upper and lower inner boxes respectively; then laminate the upper inner box paper onto the surface of the upper inner box and the lower inner box paper onto the surface of the lower inner box. S6. Disperse 1.0g of cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework in 80g of deionized water and sonicate for 30 minutes to ensure full dispersion. Then add 5.0g of polyvinyl alcohol, heat to 90℃ and stir at 500rpm until completely dissolved. Subsequently, add 20g of chitosan and 3.0g of glycerol, reduce the stirring speed to 300rpm, and continue stirring for 3 hours to obtain a coating solution. Apply the coating solution to the outer surfaces of the upper and lower inner boxes treated in step S5, with a coating thickness of 50µm, and dry and cure at 50℃. After the coating has cured, cut 6mm wide yellow ribbons and attach them to the surfaces of the upper and lower inner boxes respectively. S7. Assembly of the upper and lower cigarette boxes: Assemble the upper panel processed in step S4 and the upper inner box processed in step S6 to obtain the upper cigarette box; assemble the lower panel processed in step S4 and the lower inner box processed in step S6 to obtain the lower cigarette box; assemble the upper and lower cigarette boxes to obtain the double-layer cigarette box.

[0068] The preparation steps of the cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework include: First, dissolving 2.0 g of 2,6-pyridinedicarboxylic acid and 4.0 g of 2-methylimidazole in a mixed solvent consisting of 80 mL of N,N-dimethylformamide and 20 mL of methanol, and sonicating for 10 minutes to obtain a clear ligand solution; dissolving 3.0 g of cobalt nitrate hexahydrate in 30 mL of methanol, and slowly adding it dropwise to the ligand solution under magnetic stirring for 30 minutes; after forming a uniform pink solution, adding 2 mL of triethylamine, continuing stirring for 15 minutes, and then transferring the reaction mixture to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, and reacting at 120 °C for 49 hours. After the reaction was completed, the mixture was naturally cooled to room temperature. The resulting purple cubic crystals were collected by filtration using a Buchner funnel, washed three times with N,N-dimethylformamide and three times with methanol, and finally activated in a vacuum oven at 120°C for 7 hours to obtain a purple powdered cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework product.

[0069] The upper and lower panels provided in this embodiment use the material obtained in Preparation Example 4.

[0070] The upper inner box and lower inner box provided in this embodiment use the material obtained in Preparation Example 7. Example

[0071] This embodiment provides a manufacturing process for the aforementioned double-layer cigarette box, the steps of which include: S1. Die-cut the upper panel and the lower panel, process the V-groove, and install magnets; S2. Print four colors, hot stamp, emboss, and die-cut the upper and lower white cardboard sheets in sequence. S3. Print single-color printing and die-cutting of the yellow specialty paper inside the upper panel and the yellow specialty paper inside the lower panel respectively; S4. Using a laminating machine, the upper panel face paper processed in step S2 and the upper panel inner sticker processed in step S3 are laminated onto the upper panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied; using a laminating machine, the lower panel face paper processed in step S2 and the lower panel inner sticker processed in step S3 are laminated onto the lower panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied. S5. Die-cut, V-groove, and corner-forming the upper and lower inner boxes respectively; die-cut the yellow specialty paper for the upper and lower inner boxes respectively; then laminate the upper inner box paper onto the surface of the upper inner box and the lower inner box paper onto the surface of the lower inner box. S6. Disperse 0.8g of cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework in 75g of deionized water and sonicate for 30 minutes to ensure full dispersion. Then add 4.0g of polyvinyl alcohol, heat to 90℃ and stir at 500rpm until completely dissolved. Subsequently, add 15g of chitosan and 2.0g of glycerol, reduce the stirring speed to 300rpm, and continue stirring for 2 hours to obtain a coating solution. Apply the coating solution to the outer surfaces of the upper and lower inner boxes treated in step S5, with a coating thickness of 48µm, and dry and cure at 48℃. After the coating has cured, cut 6mm wide yellow ribbons and attach them to the surfaces of the upper and lower inner boxes respectively. S7. Assembly of the upper and lower cigarette boxes: Assemble the upper panel processed in step S4 and the upper inner box processed in step S6 to obtain the upper cigarette box; assemble the lower panel processed in step S4 and the lower inner box processed in step S6 to obtain the lower cigarette box; assemble the upper and lower cigarette boxes to obtain the double-layer cigarette box.

[0072] The preparation steps of the cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework include: First, dissolving 2.2 g of 2,6-pyridinedicarboxylic acid and 4.4 g of 2-methylimidazole in a mixed solvent consisting of 80 mL of N,N-dimethylformamide and 20 mL of methanol, and sonicating for 10 minutes to obtain a clear ligand solution; dissolving 3.3 g of cobalt nitrate hexahydrate in 30 mL of methanol, and slowly adding it dropwise to the ligand solution under magnetic stirring for 30 minutes; after forming a uniform pink solution, adding 2 mL of triethylamine, continuing stirring for 15 minutes, and then transferring the reaction mixture to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, and reacting at 120 °C for 49 hours. After the reaction was completed, the mixture was naturally cooled to room temperature. The resulting purple cubic crystals were collected by filtration using a Buchner funnel, washed three times with N,N-dimethylformamide and three times with methanol, and finally activated in a vacuum oven at 120°C for 7 hours to obtain a purple powdered cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework product.

[0073] The upper and lower panels provided in this embodiment use the material obtained in Preparation Example 5.

[0074] The upper inner box and lower inner box provided in this embodiment use the material obtained in Preparation Example 8. Example

[0075] This embodiment provides a manufacturing process for the aforementioned double-layer cigarette box, the steps of which include: S1. Die-cut the upper panel and the lower panel, process the V-groove, and install magnets; S2. Print four colors, hot stamp, emboss, and die-cut the upper and lower white cardboard sheets in sequence. S3. Print single-color printing and die-cutting of the yellow specialty paper inside the upper panel and the yellow specialty paper inside the lower panel respectively; S4. Using a laminating machine, the upper panel face paper processed in step S2 and the upper panel inner sticker processed in step S3 are laminated onto the upper panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied; using a laminating machine, the lower panel face paper processed in step S2 and the lower panel inner sticker processed in step S3 are laminated onto the lower panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied. S5. Die-cut, V-groove, and corner-forming the upper and lower inner boxes respectively; die-cut the yellow specialty paper for the upper and lower inner boxes respectively; then laminate the upper inner box paper onto the surface of the upper inner box and the lower inner box paper onto the surface of the lower inner box. S6. Disperse 1.2g of cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework in 85g of deionized water and sonicate for 30 minutes to ensure full dispersion. Then add 6.0g of polyvinyl alcohol, heat to 90℃ and stir at 500rpm until completely dissolved. Subsequently, add 25g of chitosan and 4.0g of glycerol, reduce the stirring speed to 300rpm, and continue stirring for 4 hours to obtain the coating solution. Apply the coating solution to the outer surfaces of the upper and lower inner boxes treated in step S5, with a coating thickness of 50µm, and dry and cure at 52℃. After the coating has cured, cut 6mm wide yellow ribbons and attach them to the surfaces of the upper and lower inner boxes respectively. S7. Assembly of the upper and lower cigarette boxes: Assemble the upper panel processed in step S4 and the upper inner box processed in step S6 to obtain the upper cigarette box; assemble the lower panel processed in step S4 and the lower inner box processed in step S6 to obtain the lower cigarette box; assemble the upper and lower cigarette boxes to obtain the double-layer cigarette box.

[0076] The preparation steps of the cobalt II-pyridinedicarboxylic acid-zeolite imidazole framework include: First, dissolving 1.8 g of 2,6-pyridinedicarboxylic acid and 3.6 g of 2-methylimidazole in a mixed solvent consisting of 80 mL of N,N-dimethylformamide and 20 mL of methanol, and sonicating for 10 minutes to obtain a clear ligand solution; dissolving 2.7 g of cobalt nitrate hexahydrate in 30 mL of methanol, and slowly adding it dropwise to the ligand solution over 30 minutes with magnetic stirring; after forming a uniform pink solution, adding 2 mL of triethylamine, and continuing stirring for 15 minutes, then transferring the reaction mixture to a 100 mL polytetrafluoroethylene-lined high-pressure reactor, and reacting at 120 °C for 49 hours. After the reaction, naturally cooling to room temperature, collecting the obtained purple cubic crystals by filtration through a Buchner funnel, washing three times with N,N-dimethylformamide and three times with methanol, and finally activating in a vacuum oven at 120 °C for 7 hours to obtain the final product.

[0077] The upper and lower panels provided in this embodiment use the material obtained in Preparation Example 6.

[0078] The upper inner box and lower inner box provided in this embodiment use the material obtained in Preparation Example 9.

[0079] Comparative Example 1 The specific implementation method is the same as in Example 1, except that chiral BIDIME-selenool is not added to the upper panel, lower panel, upper inner box and lower inner box.

[0080] Comparative Example 2 The specific implementation method is the same as in Example 1, except that the cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework is not added to the coating liquid.

[0081] Comparative Example 3 The specific implementation method is the same as in Example 1, except that the chiral BIDIME-selenool and cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework are not added at the same time.

[0082] Performance testing The double-layer cigarette boxes prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests according to the following method: all tests were conducted in a standard environment with a temperature of 23±2℃ and a relative humidity of 50±5%. The specific operating steps for the antioxidant performance test are as follows: Accurately weigh 10.00g of tobacco sample, place it in the test box, seal and store for 30 days. After taking it out, grind it into powder immediately, add 30mL of chloroform-methanol mixed solution (volume ratio 2:1), use an IKA MS3 vortex shaker at 2500rpm for 10min, filter through a 0.45μm organic filter membrane, take 10mL of filtrate, add 1mL of saturated potassium iodide solution, react in the dark for 5min, add 50mL of distilled water, titrate with 0.01mol / L sodium thiosulfate standard solution until pale yellow, add 1mL of starch indicator and continue titrating until the blue color disappears, record the volume of sodium thiosulfate consumed, perform three parallel tests and take the average value, calculate the peroxide value according to the formula POV=(V-V0)×C×1000 / m, where V is the volume of sodium thiosulfate consumed by the sample (mL), V0 is the blank volume (mL), C is the concentration of sodium thiosulfate (mol / L), and m is the sample mass (g).

[0083] The humidity regulation performance test was conducted using an ESPEC PL-3KT constant temperature and humidity chamber to maintain an environment of 25℃ and 80% relative humidity. The cigarette box was placed inside the chamber for 48 hours. The humidity data inside the box was recorded every 10 minutes using a Testo 635-1 temperature and humidity recorder (accuracy ±1%RH), and the maximum deviation value of all monitoring points was calculated.

[0084] Odor adsorption rate was tested by injecting 1.00 mL of 25% ammonia solution into the cigarette box using a microsyringe. After sealing for 24 hours, the solution was detected using an Agilent 7890B-5977A GC-MS system. Chromatographic conditions: DB-624UI column (30 m × 0.32 mm × 1.8 μm), injection port temperature 200 °C, detector temperature 250 °C, temperature programmed from 40 °C (hold for 5 min) at 10 °C / min to 200 °C (hold for 10 min), and quantification was performed using SIM mode with m / z=17. The residual ammonia content and adsorption rate were calculated using the external standard method.

[0085] Mechanical property testing was conducted according to GB / T1040.2-2022 standard. An Instron 5967 universal testing machine was used. A standard specimen of 50mm×10mm×1mm was made from the side wall of a cigarette box. The clamp spacing was 30mm. Tensile testing was carried out at a rate of 5mm / min. The maximum load and elongation at break were recorded to calculate the compressive strength and elongation at break.

[0086] The biodegradability test was conducted according to ISO 14855-1:2012. A 10.00g cigarette box sample was buried in a composting environment with a moisture content of 55% and maintained at a constant temperature of 58℃. After 60 days, the sample was removed, cleaned, and dried to constant weight, and the mass loss rate was calculated.

[0087] The comprehensive evaluation of the preservation effect was conducted by a panel of 10 professionally trained smokers who blindly evaluated the tobacco stored for 30 days based on four aspects: aroma intensity, degree of off-flavors, irritation, and dryness. The total score for the four aspects was 10 points, and the average score was taken as the final score.

[0088] Performance test results: Table 1: Performance test results of each embodiment and comparative example

[0089] As shown in Table 1, through comparative analysis of the performance test results of Examples 1-3 and Comparative Examples 1-3, this invention successfully solves the three major technical problems of existing cigarette boxes: limited functionality, poor preservation effect, and insufficient environmental friendliness. Specifically, Examples 1-3 achieve multiple technological breakthroughs by synergistically utilizing two functional materials: chiral BIDIME-selenool and cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework. In terms of antioxidant properties, the peroxide value of the Example group (11.9-13.8 meq / kg) is significantly lower than that of Comparative Example 1 (42.6 meq / kg) and Comparative Example 3 (65.2 meq / kg). The results (meq / kg) demonstrate that chiral BIDIME-selenool can effectively scavenge free radicals and delay the oxidation and deterioration of tobacco, solving the defect that traditional cigarette boxes cannot actively preserve freshness. In terms of humidity control, the humidity fluctuation range of the example group (±3.5-±4.2%RH) is much better than that of Comparative Example 2 (±12.3%RH) and Comparative Example 3 (±15.6%RH), indicating that the cobalt framework material can intelligently regulate the humidity of the microenvironment and overcome the problem of ordinary cigarette boxes being prone to moisture or dryness. In terms of odor adsorption, the ammonia adsorption rate of the example group (89.7-92.5%) is nearly three times higher than that of Comparative Example 3 (32.1%), confirming the high efficiency of the composite coating in capturing odor molecules and eliminating the cross-contamination phenomenon when multiple varieties of tobacco coexist. Meanwhile, the biodegradability of all groups exceeded 80%, and the mechanical properties of the example group (compressive strength 36.9-38.6 MPa, elongation at break 14.7-15.3%) showed no significant difference from the comparative group, indicating that the addition of functional materials did not affect the mechanical strength and biodegradability of the matrix material, achieving a balance between functionality and environmental friendliness. Sensory evaluation results further confirmed the technical effectiveness; the scores of the example group (8.5-8.9 points) were significantly higher than those of the comparative group (3.6-5.2 points), indicating that this design not only extends the shelf life of tobacco but also comprehensively improves the user experience. In summary, this invention, through material innovation and structural design, breaks through the limitations of the traditional single-protection mode of cigarette boxes, achieving multi-functional integration of anti-oxidation, humidity regulation, and odor adsorption, while maintaining excellent biodegradability, fundamentally solving a long-standing technical pain point in the industry.

[0090] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the present invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these modifications and improvements all fall within the scope of protection of the present invention.

Claims

1. A double-layer cigarette box, characterized in that, The cigarette box consists of an upper cigarette box and a lower cigarette box. The upper cigarette box includes an upper panel and an upper inner box, and the lower cigarette box includes a lower panel and a lower inner box. The upper and lower panels comprise the following raw materials in parts by weight: polylactic acid: 65-75 parts by weight; polyhydroxyalkanoate: 20-30 parts by weight; chiral BIDIME-selenool: 0.4-0.6 parts by weight; triethyl acetylacetate: 4-5 parts by weight. The upper and lower inner boxes comprise the following raw materials in parts by weight: polylactic acid: 70-80 parts by weight; polyhydroxyalkanoate: 15-25 parts by weight; chiral BIDIME-selenool: 0.1-0.3 parts by weight; Triethyl acetylacetic acid: 3-4 parts by weight; The surfaces of the upper and lower inner boxes are coated with a functional coating, the functional coating comprising the following raw materials in parts by weight: Cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework: 0.8-1.2 parts by weight; polyvinyl alcohol: 4-6 parts by weight; chitosan: 15-25 parts by weight; Glycerin: 2-4 parts by weight; Water: 75-85 parts by weight; The preparation method of the chiral BIDIME-selenool includes: A1, under nitrogen protection, dissolving (S)-BIDIME in anhydrous tetrahydrofuran and cooling to -76~-80℃; Add n-butyllithium and stir to obtain a reaction solution; disperse selenium powder in anhydrous tetrahydrofuran and add it dropwise to the reaction solution. After the addition is complete, heat to room temperature for reaction; A2. After the reaction is completed, the crude product obtained by rotary evaporation is purified by modified diatomaceous earth column chromatography.

2. The double-layer cigarette box according to claim 1, characterized in that, The upper and lower panels are prepared using the same method, including the following preparation steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 175°C to produce masterbatch, which was then calendered.

3. The double-layer cigarette box according to claim 1, characterized in that, The upper inner box and the lower inner box are prepared using the same method, including the following preparation steps: Chiral BIDIME-selenool was melt-blended and granulated with polylactic acid, polyhydroxyalkanoate and triethyl acetylacetate using a twin-screw extruder at a barrel temperature of 185°C to produce masterbatch, which was then calendered.

4. The double-layer cigarette box according to claim 1, characterized in that, In step A1, the reaction time at room temperature is 12-15 hours. In step A2, the preparation steps of the modified diatomaceous earth include: taking pre-dried diatomaceous earth, dispersing it in anhydrous pyridine, and cooling it to 0-5°C in an ice-water bath; adding a mixed solution of anhydrous tetrahydrofuran containing dimethylcarbamoyl chloride and p-methoxycinnamoyl chloride dropwise while stirring; after the addition is complete, raising the temperature to room temperature for reaction; after the reaction is complete, filtering the solid, washing it sequentially with water, ethanol, and ether until the filtrate is neutral, and finally drying it under vacuum at 78-82°C.

5. The double-layer cigarette box according to claim 1, characterized in that, The preparation method of the cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework includes: B1, dissolving 2,6-pyridinedicarboxylic acid and 2-methylimidazolium in a mixed solvent of N,N-dimethylformamide and methanol to obtain a ligand solution; dissolving cobalt nitrate hexahydrate in methanol and adding it dropwise to the ligand solution while stirring; after forming a homogeneous solution, adding triethylamine, transferring the reaction mixture to a high-pressure reactor lined with polytetrafluoroethylene, and reacting at 118-122℃; B2, after the reaction is completed, cooling to room temperature, washing the obtained crystals with N,N-dimethylformamide and methanol, and finally activating them under vacuum at 118-122℃.

6. The double-layer cigarette box according to claim 5, characterized in that, In step B1, the reaction time is 48-50 hours at 118-122℃.

7. The double-layer cigarette box according to claim 5, characterized in that, In step B2, the vacuum activation time at 118-122℃ is 6-8 hours.

8. A manufacturing process for a double-layer cigarette box according to any one of claims 1-7, characterized in that step... include: S1. Die-cut the upper panel and the lower panel, process the V-groove, and install magnets; S2. Print the upper and lower panel paper with four colors, hot stamping, embossing, and die-cutting respectively. S3. Print monochrome and die-cut the stickers inside the upper panel and the lower panel respectively in sequence; S4. Using a laminating machine, the upper panel face paper processed in step S2 and the upper panel inner sticker processed in step S3 are laminated onto the upper panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied; using a laminating machine, the lower panel face paper processed in step S2 and the lower panel inner sticker processed in step S3 are laminated onto the lower panel processed in step S1; then, the metal sheet is installed, the inner sticker is applied, and the screen adhesive is applied. S5. Die-cut the upper inner box and the lower inner box, process the V-groove, and form the corners; die-cut the upper inner box face paper and the lower inner box face paper; then laminate the upper inner box face paper onto the surface of the upper inner box, and laminate the lower inner box face paper onto the surface of the lower inner box. S6. Disperse the cobalt(II)-pyridinedicarboxylic acid-zeolite imidazole framework in water, then add polyvinyl alcohol and heat and stir until completely dissolved; then add chitosan and glycerin and continue stirring to obtain a coating solution; apply the coating solution to the outer surfaces of the upper and lower inner boxes treated in step S5, and dry and cure at 48-52℃; after the coating has cured, cut the ribbon and attach it to the surfaces of the upper and lower inner boxes respectively; S7. Assembly of the upper and lower cigarette boxes: Assemble the upper panel processed in step S4 and the upper inner box processed in step S6 to obtain the upper cigarette box; assemble the lower panel processed in step S4 and the lower inner box processed in step S6 to obtain the lower cigarette box; assemble the upper and lower cigarette boxes to obtain the double-layer cigarette box.

9. In the manufacturing process of the double-layer cigarette box according to claim 8, in step S6, the coating thickness of the coating liquid applied to the outer surfaces of the upper and lower cigarette boxes is 48-52 μm.

10. In the manufacturing process of the double-layer cigarette box according to claim 8, in step S6 and step S7, the continuous stirring time is 2-4 hours.